Laboratory Study of the Effect of Salinity on the Demulsification Process in High Temperature Crude Oil - Denny Aditya Rachman; Havidh Pramadika; Samsol Samsol (Penerbitan Universitas Trisakti, 2020)
In the process of drilling and servicing oil wells, KCl and NaCl used to provide hydrostatic pressure into the bowels of the earth. The brine solution was produced accidentally to the surface facility when the oil lifting process was carried out and induces the thickness of the oil-water emulsion in the separation tank. Emulsions must be broken down into oil and water phases so that they do not interact with the oil treatment process in the refinery unit. Emulsion stability was influenced by pH, salinity, temperature and concentration of asphaltene, resin and wax. The purpose of this study was to determine the effect of salinity on the oil-water demulsification process. This research was conducted by varying the salinity of 5%, 15%, 25%, and 35% in a 100 ml oil-water emulsion sample with a ratio of 1: 1 oil and water. Demulsification of the emulsion sample using the precipitation method for 120 minutes by recording the% of oil volume separate every 20 minutes, at temperatures of 30 ° C and 110 ° C. The higher the temperature given, the more stable the emulsion in crude oil. From the final result after 120 minutes of pricipitation shows that the emulsion separation process which influenced by NaCl salinity is more difficult than the effect of KCl salinity.